2017
DOI: 10.1038/modpathol.2016.181
|View full text |Cite
|
Sign up to set email alerts
|

MUC4, a novel immunohistochemical marker identified by gene expression profiling, differentiates pleural sarcomatoid mesothelioma from lung sarcomatoid carcinoma

Abstract: Sarcomatoid mesothelioma, a histological subtype of malignant pleural mesothelioma, is a very aggressive tumor with a poor prognosis. Histological diagnosis of sarcomatoid mesothelioma largely depends on the histomorphological feature of spindled tumor cells with immunohistochemical reactivity to cytokeratins. Diagnosis also requires clinico-radiological and/or macroscopic evidence of an extrapulmonary location to differentiate it from lung sarcomatoid carcinoma. Although there are promising immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
0
21
2
Order By: Relevance
“…MUC4 plays a role in cell differentiation rather than cell proliferation of the normal goblet cells, the stratified squamous epithelial cells, and malignant epithelial tumor cells 19 . We previously reported the MUC4 expression in sarcomatoid carcinoma of the lung and its utility to differentiate from sarcomatoid mesothelioma 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC4 plays a role in cell differentiation rather than cell proliferation of the normal goblet cells, the stratified squamous epithelial cells, and malignant epithelial tumor cells 19 . We previously reported the MUC4 expression in sarcomatoid carcinoma of the lung and its utility to differentiate from sarcomatoid mesothelioma 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed the utility of MUC4 to distinguish epithelioid mesothelioma from lung adenocarcinoma and squamous cell carcinoma. We have previously reported the MUC4 expression in sarcomatoid carcinoma of the lung and its utility to differentiate from sarcomatoid mesothelioma 20 . In our previous report, we emphasized the MUC4 expression in spindled cells of sarcomatoid carcinoma of lung.…”
Section: Discussionmentioning
confidence: 99%
“…However, interpretation should be with caution when differentiating pleural MM from lung small cell carcinomas (SCC), because it was reported that D2-40 can stained 77% of lung SCC [ 5 ]. Recently, novel markers, such as BAP1 [ 5 ], MUC4 [ 35 ], fibulin-3 [ 41 ], have been used to improve the diagnostic accuracy of D2-40 for pleural MM.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin and other positive markers of MPM were negative, and no specific tendency for differentiation was noted. For differentiation from lung sarcomatoid carcinoma, we performed MUC4 and GATA binding protein 3 (GATA3) staining . MUC4 was negative and GATA3 was partially positive (Fig.…”
mentioning
confidence: 99%
“…Recently, however, it was reported that MUC4 and GATA3 are useful for such differentiation. Amatya et al . found that MUC4 was expressed in 0 of the 31 sarcomatoid MPM and in 21 of the 29 lung sarcomatoid carcinoma (5 cases of spindle cell carcinoma and 24 of pleomorphic carcinoma).…”
mentioning
confidence: 99%